Primary Central Nervous System Vasculitis Mimicking Brain Tumor. Issue 4 (November 2015) - Lin, Bon-Jour; Ma, Hsin-I
Abstract : Primary central nervous system vasculitis (PCNSV) is a rare disease with a nonspecific and expansive spectrum of clinical manifestations. A 40-year-old woman presented with acute onset of severe headache associated with nausea. Computed tomography of the brain showed 1 solitary hypodense parenchymal lesion over the left temporal lobe with an internal fluid level. A brain magnetic resonance imaging showed the presence of 1 isointense parenchymal lesion on T1-weighted and T2-weighed images, with surrounding brain edema. The patient accepted craniotomy for excision of lesion under the preoperative impression of brain tumor with hemorrhagic transformation. The pathologic report was extensive vasculitis with hemorrhagic infarction. The diagnosis of PCNSV was made after exclusion of secondary causes–related vasculitis and hereditary hypercoagulant status. This report highlights that PCNSV could appear as a hemorrhagic tumor-like lesion on neuroimaging. Considering PCNSV in the differential diagnosis is important in patients suspected with cerebral hemorrhage, cerebral thrombosis, or brain tumor.